2014
DOI: 10.1378/chest.13-2110
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes After In-Hospital CPR in Older Adults With Chronic Illness

Abstract: BACKGROUND:Outcomes aft er in-hospital CPR in older adults with chronic illness are unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
3
22
1
3
Order By: Relevance
“…In this study, 55% of patients were male. Stapleton et al conducted a study to compare the result of CPR in patients with or without chronic diseases and found that patients suffering from chronic illnesses had a smaller chance of surviving cardiopulmonary arrest (P <0.001) (14). This was also the case in our study, but exact information is needed to make comparisons.…”
Section: Discussionsupporting
confidence: 63%
“…In this study, 55% of patients were male. Stapleton et al conducted a study to compare the result of CPR in patients with or without chronic diseases and found that patients suffering from chronic illnesses had a smaller chance of surviving cardiopulmonary arrest (P <0.001) (14). This was also the case in our study, but exact information is needed to make comparisons.…”
Section: Discussionsupporting
confidence: 63%
“…Oznacza to, że szansa na przeżycie po skutecznej resuscytacji jest większa niż w ogólnej populacji osób, u których dochodzi do NZK (54% v. 74,2%). Obserwacje te znajdują swoje potwierdzenie w innych pracach mówiących o skuteczności czynności resuscytacyjnych po wewnątrzszpitalnym NZK (52−62) i towarzyszącej śmiertelności szpitalnej (64−89) [11]. Ocena skuteczności resuscytacji w przypadku użycia innych kodów NZK niż I46.0 jest niemożliwa na podstawie danych zebranych w niniejszej pracy.…”
Section: Dyskusjaunclassified
“…Można to wyjaśnić szybkim rozpoznaniem NZK, szybszym podjęciem kwalifikowanych czynności resuscytacyjnych, niższym wiekiem pacjentów oraz faktem monitorowania czynności życio-wych w chwili wystąpienia NZK. Niektóre badania wskazują, że do 45% wszystkich przypadków wewnątrzszpitalnych zatrzymań krążenia ma miejsce na OIT [11]. Odsetek ten, w przypadku pacjentów leczonych na polskich OIT, jest na zbliżonym poziomie.…”
Section: Dyskusjaunclassified
“…For example, in the arrested and died category (typically involving an unaccompanied 'elderly' adult patient whose cardiac rhythm showed prolonged PEA or asystole), alignment of the trajectories was straightforward. When chronic and terminal illnesses exist, these are associated with much poorer outcomes (Stapleton et al, 2014: Cadogen, 2010) and persistent asystole for over twenty minutes despite ongoing ALS, in the absence of a reversible cause is considered reasonable grounds to stop resuscitation (Resuscitation Council (UK), 2015). These `subtacular' deaths were not preventable by the application of advanced medical technology and as noted by Bailey et al (2011), do not fit with the ethos of emergency care.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rates for cardiac arrest outside of hospital are around 1% to 8% (Resuscitation Council (UK), 2015; Clarke, Lyon, Short, Crookston, & Clegg 2014; Herlitz et al, 2006) and fewer than 20% of patients arresting in hospital will survive to discharge (Stapleton, Ehlenbach, Deyo, & Curtis, 2014;Resuscitation Council (UK), 2011). Overall survival rates have not significantly changed for decades and are especially poor when associated with advanced chronic disease (British Medical Association (BMA), 2014; Gaieski, Abella, & Goyal, 2012).…”
Section: Introductionmentioning
confidence: 99%